Presurgical nasoalveolar molding: A boon to facilitate the surgical repair in infants with cleft lip and palate - Prabhakar Ramasetty Attiguppe; Y M Karuna; Chandrashekar Yavagal; Saraswathi V Naik; B M Deepak; Rekhamani Maganti; Chaithanya G Krishna (Wolters Kluwer Medknow Publications, 2016)
Cleft lip and palate (CLP) is the most common congenital craniofacial anomaly. Rehabilitation of CLP generally requires a team approach. Alveolar and nasal reconstruction for these patients is a challenge for the reconstructive surgeon. Various procedures have been attempted to reduce the cleft gap, so as to obtain esthetic results postsurgically. The presurgical nasoalveolar molding (PNAM) technique, developed by Grayson, is a new approach to presurgical infant orthopedics. PNAM reduces the severity of the initial cleft alveolar and nasal deformity. Thus, it enables the surgeon and the patient to enjoy the benefits associated with repair of a cleft deformity that is minimal in severity. This article presents a brief insight into PNAM with a case series of three different cases (one unilateral and two bilateral) which underwent PNAM treatment and gave an excellent surgical prognosis.